2023
DOI: 10.1007/s00122-023-04322-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of maternal environment-dependent expression-QTLs of tomato seeds

Abstract: Seeds are essential for plant reproduction, survival, and dispersal. Germination ability and successful establishment of young seedlings strongly depend on seed quality and on environmental factors such as nutrient availability. In tomato (Solanum lycopersicum) and many other species, seed quality and seedling establishment characteristics are determined by genetic variation, as well as the maternal environment in which the seeds develop and mature. The genetic contribution to variation in seed and seedling qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
2
2
0
Order By: Relevance
“…We observed that 49.64% (29,623 of a total 59,669) of cis -eQTLs were common in both environments, as compared to 18.62% (25,528 of a total 137,100) of trans -eQTLs; this result was robust to FDR cutoff (FDR of 0.01 and 0.05). Moreover, this is consistent with previous observations from studies on other species that have found 48%−77% overlapping cis -eQTLs and 9%−60% common trans -eQTLs across environments ( Smith and Kruglyak, 2008 ; Snoek et al, 2012 ; Sterken et al, 2023 ). It further indicates that trans -eQTLs might be more environment-specific than cis -eQTLs.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that 49.64% (29,623 of a total 59,669) of cis -eQTLs were common in both environments, as compared to 18.62% (25,528 of a total 137,100) of trans -eQTLs; this result was robust to FDR cutoff (FDR of 0.01 and 0.05). Moreover, this is consistent with previous observations from studies on other species that have found 48%−77% overlapping cis -eQTLs and 9%−60% common trans -eQTLs across environments ( Smith and Kruglyak, 2008 ; Snoek et al, 2012 ; Sterken et al, 2023 ). It further indicates that trans -eQTLs might be more environment-specific than cis -eQTLs.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, this is consistent with previous observations from studies on other species that have found 48%-77% overlapping cis-eQTLs and 9%-60% common trans-eQTLs across environments (Smith and Kruglyak, 2008;Snoek et al, 2012;Sterken et al, 2023). It further indicates that trans-eQTLs might be more environment-specific than cis-eQTLs.…”
Section: Genetic Architecture Of Gene Expression Variationsupporting
confidence: 92%
See 1 more Smart Citation
“…Seed germination and storage methods are crucial for optimal plant growth and sustainable agriculture [9]. While soil and peat have traditionally been used, there is a growing need for ecological alternatives.…”
Section: Introductionmentioning
confidence: 99%